Calculation of the Molecular Weight of a Polymer by the Experimental Method - H.A. Khaydarova (Genius Journals, 2023)
The article describes the most convenient and simple process - the viscometric method for the experimental determination of the molecular weight of a polymer. With the introduction of the developed methodology in the laboratory practice of the chemistry of macromolecular compounds, the comprehensibility of students will average 72-89%.
Keywords: molecular compounds; molecular weight; solubility